The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1969
DOI: 10.1111/j.1365-2621.1969.tb00918.x
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Properties of Post‐Mortem Muscle. 7. Changes in Nonprotein Nitrogen and Free Amino Acids of Bovine Muscle

Abstract: SUMMARY– Proteolysis and its relationship to tenderness were studied by measuring nonprotein nitrogen (NPN), free amino groups, and shear resistance during post‐mortem aging of bovine muscle. Both NPN and free amino groups increased during post‐mortem aging, indicating some degradation of proteins and/or peptides. However, neither the increase in NPN nor free amino groups was related to post‐mortem tenderization since these quantities increased only after most of the improvement in tenderness had occurred. Muc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

1977
1977
2013
2013

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 45 publications
0
14
0
Order By: Relevance
“…This further demonstrates that significant changes in tenderness occur early during postmortem aging. It could be argued that if aging was carried out for a longer time, significant changes could have been detected in tenderness; however, our earlier work demonstrated that W-B shear values change little between 7 and 28 days of postmortem time (Parrish et al, 1969).…”
Section: Discussionmentioning
confidence: 97%
“…This further demonstrates that significant changes in tenderness occur early during postmortem aging. It could be argued that if aging was carried out for a longer time, significant changes could have been detected in tenderness; however, our earlier work demonstrated that W-B shear values change little between 7 and 28 days of postmortem time (Parrish et al, 1969).…”
Section: Discussionmentioning
confidence: 97%
“…Many studies have shown the changes of FAA during storage. Isoleucine, tyrosine, valine, threonine + leucine and aspartic acid + phenylalanine increased as much as four‐ to six‐fold during storage (Parrish et al . 1969), but large increments were observed on alanine, threonine + leucine and lysine in the Parrish et al .…”
Section: Discussionmentioning
confidence: 99%
“…Parrish et al ( 1969b) reported that the aging of beef for 4 days at 2'C is accompanied by large increases in Ala, Val, Glu and Lys. Field et al ( 197 1) reported that large increases in Val, Thr+Ser, Glu, Leu, and Lys are obtained by the aging ofbeef at 2'C for 5 days.…”
Section: Improvement Of Meat Tastementioning
confidence: 99%